Linguo-Pragmatic Features Of Personal Pronouns - Pardaev Zafar; Uralova Ruxshona (Peerian Journals Publishing, 2024)
This work analyzes the stylistic-pragmatic conditions that give rise to various shades of personal pronouns, as well as the linguistic and extralinguistic factors that bring these possibilities to fruition. It highlights the role and importance of pronouns in the speech process in the Uzbek language, examining their unique stylistic, communicative-pragmatic characteristics and possibilities in specific contexts and speech situations.
Keywords: Linguistic-pragmatic speech act; evaluation; intention; communicative situation